GURU DAN MOTIVASI BELAJAR AGAMA ANAK TUNA GRAHITA - Etik Kurniawati (Wahana Akademika: Jurnal Studi Islam dan Sosial, 2016)
AbstractReligious Education given to children with intellectual challenges are di? erent from normal children in general. Th e di? erence is not in its subject matter, but in terms of the extent and development of materials of religious education tailored to the child’s ability. A Mentally dissabled child is not easy to be educated about the teaching of religion, because the limitations in capturing the religious instruction and behavior di? erent from normal children. Teachers have an important character such as a motivator. Teachers should be able to increase or stimulate activity, provide encouragement, as a good example, as well as providing facilities for students to have a passion in studying religion, especially in the process of learning in children with intellectual challenges who have mental conditions that are di? erent from normal children. Th erefore, it is important for teachers to give encouragement or stimulus that they have a passion and interest in the study of religion.Keywords: Teacher, Motivation, Mentally disabled.